Enforcement of the Code Of Ethics of Pharmacist Proffesion in Kabupaten Sidoarjo: Penegakan Kode Etik Profesi Apoteker di Kabupaten Sidoarjo - Hamdani, Ulfa Nuraini; Purwaningsih, Sri Budi (Universitas Muhammadiyah Sidoarjo, 2021)
This study raises the formulation of the problem on how to Enforce the Code of Ethics of the Pharmacist Profession in Sidoarjo Regency and how the Ethical Accountability can be imposed on Pharmacists if they commit a violation. Pharmacists namely PC IAI Sidoarjo Regency and MEDAI D East Java were then linked to existing regulations and libraries, based on the analysis conducted, it was found that the enforcement of the code of ethics for the pharmacist profession in Sidoarjo Regency is the responsibility of the East Java Regional MEDAI, besides that there is still a lack of open access for the community. as well as a monitoring pattern that is only based on complaints, besides that, it is also found that there is a distribution of criteria for violations in the implementing regulations that are not specifically explained, based on the results of the analysis, it can be concluded that enforcement The code of ethics for the pharmacist profession in the district still tends to be passive because it is only based on complaints without direct supervision.